Motivasi Masyarakat Palangka Raya Dalam Pelaksanaan Tradisi Menunggu Kuburan Dalam Tinjauan Hukum Islam - Kusuma Kusuma (LP2M IAIN Palangka Raya, 2015)
This study describe what lies behind the people of Palangkaraya carry out the tradition of waiting for the grave, the procedure of the implementation process waiting grave, awaiting a review of Islamic traditions graves in Palangkaraya. The method in this study the author uses descriptive qualitative approach. Batamat is last in the procession this tradition in which its implementation families prepare and sticky rice. In the execution authors found ethics or behavior that can not be justified performed by people who await the grave is sleeping on top of the grave. Tradition waite these graves can be said urf Saheeh because tradition is intended effort of a weak servant of Allah, to pray for the people who are in the grave so that God's mercy for the deceased, aims In order to maintain the graves to prevent theft and does not result in harm those who carry out the tradition of waiting for the tomb, While the tradition waite these graves can be said urf elements are imperfect caused harm to people waiting tombs, such as the implementation of people waiting grave so sick. Constituted with the intention that does not rely upon Allah.